Competitiveness of Germany's Economic and Political Space - Vladislav B. Belov (Современная Европа)
Germany's economic Standort, as a crucial component of the European Union's broader economic and political space, largely shapes its competitiveness. In his September 2024 report on this topic, Mario Draghi gave special, though understandibly insufficient, attention to Germany's role. This article aims to provide a comprehensive analysis of the competitive strengths and weaknesses of Germany's economy. The author employs a spatial approach, viewing the German economy as a Standort product, intentionally shaped by the executive and legislative authorities at all levels, in collaboration with key stakeholders from business, academia, education, and active segments of civil society. The author concludes that inefficiencies in the federal government's economic and political activities, including inadequate dialogue with stakeholders, along with structural problems accumulated over recent decades in the national economy, have been major contributors to the decline in Germany's competitiveness. Prospects for reversing this negative trend remain uncertain. Without stronger leadership in Berlin and more effective Standort collaboration, there is a risk that Germany in the medium term.may continue to be the «sick man of Europe».